Integrated strategies of participatory surveillance to promote flu vaccine coverage in HCWs. (30th September 2020) - Rizzo, C; Zaffina, S; Vinci, M R; Santoro, A; Gilardi, F; Ciampini, S; Pandolfi, E; Campagna, I; Carsetti, R; Raponi, M
Abstract: Problem: Influenza represents a threat for healthcare facilities where sudden outbreaks of illness can lead to high morbidity and mortality in vulnerable patients and increase absenteeism in HCWs. Despite WHO recommends annual influenza vaccination of HCWs, flu vaccine coverage (FVC) remain very low in most EU countries. Description of the Problem: Despite an important increase in FVC recorded in last years in our hospital, FVC remains under 75%. We pilot a prospective cohort study in HCWs in order to test new methods for influenza vaccination promotion. We create a web-based system integrating information on vaccination status (unvaccinated HCWs, 1/2/3 years vaccinated ones) and demographic data. The Hospital Ethical Committee approved the study. During the 2019/20 influenza season we nested a test-negative case-control study in the cohort to evaluate Influenza vaccine effectiveness against influenza-like-illness (ILI) laboratory confirmed as influenza in HCWs. Results: A total of 443 on 2675 HCWs were recruited in the cohort and weekly received specific SMS messages and phone call for a personal invitation to get flu shot. The median age of the cohort was 43, 3 (range 21-72) with 128 male (28, 9%). In the cohort a FVC of 26/205 (12, 7%) was registered in HCWs never vaccinated in the previous 3 seasons. Nasopharyngeal swabs were distributed to 205 subjects for influenza confirmation and they received weekly messages in order to check their health status remanding to self-swab in the case of ILI symptoms. Lessons: Using a new and integrated strategy for influenza vaccination promotion in HCWs can increase the FVC. The use of personal direct messages to HCWs and the possibility of confirming or excluding influenza in case of ILI symptoms in those vaccinated and unvaccinated, seems to be very effective in increasing vaccine coverage. Moreover, the cohort could be also used for further research studies as for example the effect of repeated influenza vaccination. Key messages: The presented practice appears to be effective and could be applied to larger HCWs population. This strategy could be considered as a good practice of workplace vaccination promotion.